2015
DOI: 10.1039/c5cc06585b
|View full text |Cite
|
Sign up to set email alerts
|

A quinary layer transition metal oxide of NaNi1/4Co1/4Fe1/4Mn1/8Ti1/8O2 as a high-rate-capability and long-cycle-life cathode material for rechargeable sodium ion batteries

Abstract: A well-crystallized single-phase quinary layer transition metal oxide of NaNi1/4Co1/4Fe1/4Mn1/8Ti1/8O2 was successfully synthesized. It exhibited excellent cycle performance and high rate capability as a cathode material for sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…The electrochemical Na-ion intercalation behavior of layered transition-metal oxides was examined by Delmas and co-workers in the early 1980s. The significant role of the inactive Ti ions in promoting the battery performance of layered sodium-containing electrodes is also found in other reports [39][40][41][42] and has been reviewed in a previous paper. However, these authors have identified many structural properties of layered and trigonal-prismatic interstitial sites, respectively.…”
Section: Layered Transition-metal Oxidessupporting
confidence: 64%
See 1 more Smart Citation
“…The electrochemical Na-ion intercalation behavior of layered transition-metal oxides was examined by Delmas and co-workers in the early 1980s. The significant role of the inactive Ti ions in promoting the battery performance of layered sodium-containing electrodes is also found in other reports [39][40][41][42] and has been reviewed in a previous paper. However, these authors have identified many structural properties of layered and trigonal-prismatic interstitial sites, respectively.…”
Section: Layered Transition-metal Oxidessupporting
confidence: 64%
“…The cycle life after 100 electrochemical cycles can be 93.2%, and more than 60% of the initial discharge capacity can be achieved even at a rate of 5 C. During the charging/discharge process, the Ni redox changes between divalent and tetravalent, while the Ti ions remain tetravalent. The significant role of the inactive Ti ions in promoting the battery performance of layered sodium‐containing electrodes is also found in other reports and has been reviewed in a previous paper …”
Section: Cathode Materialsmentioning
confidence: 98%
“…They found that P2 + O3 integration can be easily generated when a certain amount of Li + is doped into the TMO 2 layers. Yue et al introduced the quinary layered NaNi 1/4 Co 1/4 Fe 1/4 Mn 1/8 Ti 1/8 O 2 as high rate capability material . The charge/discharge curves are much smoother than those of single or binary iron‐containing oxides.…”
Section: Iron‐ and Mn‐based Layered Oxide Cathodesmentioning
confidence: 99%
“…O3‐NaFe 0.3 Ni 0.7 O 2 delivers an initial discharge capacity of 135 mAh g −1 with most of the capacity located in a high‐voltage region of 2.5–3.8 V . O3 layered materials with various transition metal compositions have also been studied; for example, Fu and co‐workers have reported on the Fe–Co–Ni–Ti and Fe–Co–Ni–Ti–Mn systems, which demonstrate a long‐term cyclability and a high rate capability . Hu and co‐workers have reported an air‐stable and Co/Ni‐free layered metal oxide of O3‐Na 0.9 [Cu 0.22 Fe 0.30 Mn 0.48 ]O 2 , which exhibits a reversible capacity of 100 mAh g −1 at an average storage voltage of 3.2 V with a long cycle life .…”
Section: Cathode Materialsmentioning
confidence: 99%